Cardiogram of the Park: Quantitative Analysis of Walking Scenarios of Trakų Vokė Historic Park - Zaleckis, Kęstutis; Gražulevičiūtė-Vileniškė, Indrė; Armağan Doğan, Huriye; Ivashko, Yulia (Landscape Architecture and Art, 2023)
In this research, the concept of isovist [1,6] was employed to analyze spaces of the park as a container and catalyser of human activities and experiences in quantitative terms. The concept of the isovist defines the visual environment as a system of objects that structures the light as a source of stimuli for human perception. Trakų Vokė ensemble was selected as a case study object to test this quantitative approach towards historic park analysis. Methods of the research include a literature review on specific characteristics of Trakų Vokė ensemble, observation on site, analysis of available maps and satellite images, development of linear drawing of the park using AutoCAD, modelling using Isovist_App and ESRI ArcMap software, analysis, and discussion of results. The research has demonstrated that the results of the isovist and visual graph-based analysis reflect the observed spatial features of Trakų Vokė Park quite well and can be used for various purposes, including a more detailed description of valuable features of heritage objects, a detailed comparison between different parks, simulative reconstruction of the character of the historical park in the past based on historical data, maintenance and management of the park, parametric design of landscape spaces, etc.